Low Level Laser Effect in Treatment of Patients with Intractable Tinnitus Due To Sensorineural Hearing Loss - Mirvakili, Abbas; Mehrparvar, Amirhoushang; Mostaghaci, Mehrdad; Mollasadeghi, Abolfazl; Mirvakili, Masud; Baradaranfar, Mohammadhosein; Dadgarnia, Mohammadhosein; Davari, Mohammadhosein (Journal of Lasers in Medical Sciences, 2014)
Introduction: Tinnitus is defined as a perception of sound without an external acoustic stimulus. Due to large number of causes and limited knowledge of its pathophysiology, tinnitus still remains an obscure symptom. Methods: This was a cross-sectional study on 120 patients with tinnitus and sensorineural hearing loss who were randomly divided into two groups; one group received low-level laser and the second group used the same instrument but off, for 20 sessions of 20 minutes. A tinnitus handicap inventory (THI) and Visual Analog Scale (VAS) were used to evaluate the severity of patients' symptoms. Severity and frequency of tinnitus were also determined using Audiometric tests. Results: The average age of the 120 patients in the two groups of study were not statistically significantly different. The mean difference of severity of tinnitus between the two groups was statistically significant at the end of the study and 3 month after completion of treatment. The VAS and THI mean differences after the treatment were statistically significant between the two groups but not statistically significant after 3 months of completion the study. Conclusion: Low level laser radiation is effective for short-term treatment of Tinnitus caused by sensorineural hearing loss and its impact may be reduced over the time.